2018
DOI: 10.22460/pej.v2i2.1008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Learning Media and the Ability to Think Creative of to the Ability to Science Literacy Student of Elementary School

Abstract: This study aims to determine the effect of the learning media and the ability to think creative of to the ability to science literacy student of elementary school. The study was conducted at the grade V SDN Manangga and SDN Tenjonagara Kabupaten Sumedang. Research design using experiment method with treatment by level 2 x 2. Data analysis is the two way anava. The results of this study indicate that (1) There were differences in the ability to science literacy of student of study by using ICT media with educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
1
9
0
4
Order By: Relevance
“…Aplikasi pembelajaran multimedia interaktif merupakan salah satu media pendukung dalam proses belajar mengajar yang menggabungkan semua media dari mulai text, gambar, video, animasi, audio dan games. Ilmu Pengetahuan Alam (IPA) merupakan salah satu mata pelajaran yang membutuhkan dukungan media pembelajaran interaktif, karena mata pelajaran ini sulit dijelaskan hanya dengan menggunakan text dan gambar saja [3]. Pada penelitian mengenai pengaruh media pembelajaran interaktif terhadap hasil belajar siswa menyatakan bahwa 23,89% siswa mengalami peningkatan terhadap hasil belajar IPA, 39,44% menyatakan multimedia interaktif membantu proses belajar dan 41,77% menyatakan bahwa mata pelajaran biologi menjadi lebih menarik untuk dipelajari dengan adanya media pembelajaran interaktif [4].…”
Section: Pendahuluanunclassified
“…Aplikasi pembelajaran multimedia interaktif merupakan salah satu media pendukung dalam proses belajar mengajar yang menggabungkan semua media dari mulai text, gambar, video, animasi, audio dan games. Ilmu Pengetahuan Alam (IPA) merupakan salah satu mata pelajaran yang membutuhkan dukungan media pembelajaran interaktif, karena mata pelajaran ini sulit dijelaskan hanya dengan menggunakan text dan gambar saja [3]. Pada penelitian mengenai pengaruh media pembelajaran interaktif terhadap hasil belajar siswa menyatakan bahwa 23,89% siswa mengalami peningkatan terhadap hasil belajar IPA, 39,44% menyatakan multimedia interaktif membantu proses belajar dan 41,77% menyatakan bahwa mata pelajaran biologi menjadi lebih menarik untuk dipelajari dengan adanya media pembelajaran interaktif [4].…”
Section: Pendahuluanunclassified
“…UNESCO defines ICT as a combination of information technology and information technology. Whereas Halidi (in Kelana, 2018) say that ICT media is a means that can help teachers to convey messages / information or transfer knowledge to students. It can be concluded that ICT media is a medium that can be used by a teacher in disseminating all information with the help of technology.…”
Section: Ict Mediamentioning
confidence: 99%
“…Starting from conscious effort and culminating in the process of forming attitudes developing the noble intelligence and skills of students according to their needs. According to Amiq (in Putri, et al;2018), the media can be packaged in the form of physical objects which then convey the message. Sadiman (Ulfah, 2013) mentions that there are four types of media that are often used when learning, namely games, illustration media, audio, and silent projection.…”
Section: Introductionmentioning
confidence: 99%
“…According to Amalana (in Handayani, et al 2018), the approach taken by teachers to students using conventional methods is out of sync with the development faced by children in school. According to Kelana (2018) Learning is not a teacher-dominated process, but requires students to be active and creative in carrying out a number of activities. Thus, teachers must make innovations and innovations in learning activities, namely by choosing learning media that can make students active and easy to understand in mathematics.…”
Section: Introductionmentioning
confidence: 99%